Organic Nanophotonics Fundamentals and Applications - Zhao, Yong Sheng; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This comprehensive text collects the progress made in recent years in the fabrication, processing, and performance of organic nanophotonic materials and devices. The first part of the book addresses photonic nanofabrications in a chapter on multiphoton processes in nanofabrication and microscopy imaging. The second part of the book is focused on nanoscale light sources for integrated nanophotonic circuits, and is composed of three chapters on organic nano/microcavities, organic laser materials, and polymer light-emitting electrochemical cells (LECs). The third part is focused on the interactions between light and matter and consists in three chapters, including the propagation of light in organic nanostructures and photoswitches based on nonlinear optical polymer photonic crystals and photoresponsive molecules, respectively. The final chapter of this book introduces the integration of miniaturized photonic devices and circuits with various organic nanophotonic elements. The practical case studies demonstrate how the latest applications actually work, while tables throughout the book summarize key information and diagrams and figures help readers to grasp complex concepts and designs. The references at the end of each chapter can be used as the gateway to the relevant literature in the field. Moreover, this book helps researchers to advance their own investigations to develop the next generation of miniaturized devices for information processing, efficient energy conversion, and highly accurate sensing. Yong Sheng Zhao, PhD, is a Professor at the Institute of Chemistry, Chinese Academy of Sciences (ICCAS), China.
Multiphoton Process in Nanofabrication and Microscopy Imaging -- Strongly Coupled Organic Microcavities -- Crystalline Organic Materials toward Laser Application -- Stable Junction Polymer Light-Emitting Electrochemical Cells -- Miniaturized Photonic Circuit Components Constructed from Organic Dye Nanofiber Waveguides -- Nonlinear Optical Polymer Photonic Crystals and their Applications -- Mastering nano-objects with photoswitchable molecules for nanotechnology applications -- Design, Fabrication and Optoelectronic Performance of Organic Buiding Blocks for Integrated Nanophotonic Devices.
Keywords: Materials science; Physical chemistry; Lasers; Photonics; Optical materials; Electronic materials; Nanotechnology; Materials Science; Nanotechnology; Laser Technology, Photonics; Physical Chemistry; Optical and Electronic Materials; Electronic books